Geometrical design of a two-stroke marine diesel engine crosshead bearing with natural fibre composite material - Yiow, Ru Vern (2022)
Current two-stroke marine diesel engine crosshead bearings are steel backed with tin based white metal overlayed, similar to conventional journal bearings. With increased environmental pressure, the shift to more sustainable material industries globally including the maritime gained much attention as a renewable source and bio friendliness. However, they have been shown to demonstrate lower mechanical properties compared to conventional material such as steel. A proposed crosshead bearing design idea using NFC as bearing material needs to satisfy several mechanical conditions, namely in this research, the ability to withstand a vertical downward load of 1469 kg, the weight of a 60 cm bore piston and piston rod assembly. The idea generation of the proposed crosshead design was performed with the TRIZ (Theory of Inventive Problem Solving) method combined with Biomimetics. Four conceptual designs were ideated and modelled virtually using ANSYS. The best design selection was performed using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The final successful ideated design was obtained capable of withstanding the mentioned load with the Relative Closeness to the Ideal Solution score of 0.929. The ideation process together with simulation provided evidence that there is potential of utilising Kenaf, with a score of 0.955, and Polyhydroxybutyrate (PHB), with a score of 0.928, as suitable natural fibre material and polymer for highly rated engine components in marine diesel engines.